2020
DOI: 10.3390/math8020181
|View full text |Cite
|
Sign up to set email alerts
|

Strong Solutions of the Incompressible Navier–Stokes–Voigt Model

Abstract: This paper deals with an initial-boundary value problem for the Navier–Stokes–Voigt equations describing unsteady flows of an incompressible non-Newtonian fluid. We give the strong formulation of this problem as a nonlinear evolutionary equation in Sobolev spaces. Using the Faedo–Galerkin method with a special basis of eigenfunctions of the Stokes operator, we construct a global-in-time strong solution, which is unique in both two-dimensional and three-dimensional domains. We also study the long-time asymptoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…The existence and uniqueness of strong solutions of the incompressible Navier-Stokes-Voigt model is studied in [3].…”
Section: Lemma 27 (Strong Monotonicity (Sm) and Local Lipschitz Conti...mentioning
confidence: 99%
See 1 more Smart Citation
“…The existence and uniqueness of strong solutions of the incompressible Navier-Stokes-Voigt model is studied in [3].…”
Section: Lemma 27 (Strong Monotonicity (Sm) and Local Lipschitz Conti...mentioning
confidence: 99%
“…The new term in our model has similarity to the Voigt term used in Voigt/Kelvin‐Voigt/Kelvin Model [41] for viscoelastic fluids. There has been lot of recent works on Voigt Model, see for example [3, 21, 24, 25]. Recently, Rong et al [38] and Berselli et al [4] all studied the extension of the Baldwin and Lomax model [2] to non‐equilibrium (ddtoversetu20$$ \frac{d}{dt}\overline{{\left\Vert {u}^{\prime}\right\Vert}^2}\ne 0 $$, for a precise definition see equilibrium) problems.…”
Section: Introductionmentioning
confidence: 99%
“…Using techniques similar to the ones in the proof of Theorem 1 from [8], it can be shown that problem (26) has a unique solution (v, p) in the space E(Q T ). Consequently, equation (24) is solvable.…”
Section: Operators Related To the Linear Part Of The Generalized Navi...mentioning
confidence: 99%
“…• The Navier-Stokes-Voigt equations (Kelvin-Voigt type viscoelastic fluids) when δ = 1, µ 0 > 0, µ 1 > 0, η ≡ 0 (see [6][7][8][9]); •…”
mentioning
confidence: 99%
“…In the literature, some authors have referred the system ()–() as system of Navier–Stokes–Voigt equations (see, e.g., Baranovskii 25 and Kalantarov and Titi 26 ), since the system can be considered as a regularization of Navier–Stokes equations by ϰ 27 . Various inverse problems for the Navier–Stokes equations were considered in many works, for example, previous works 6,7,28–33 and references therein.…”
Section: Introductionmentioning
confidence: 99%